Efficacy of a respiratory syncytial virus vaccine candidate in a maternal immunization model - Jorge C. G. Blanco (Nature Portfolio, 2018)
RSV infection is a major cause of bronchiolitis in infants and maternal vaccination is a potential preventive option. Here, Blanco et al. show efficacy of a Newcastle disease virus-based virus-like particle vaccine candidate in naive and pre-exposed cotton rat dams and their offspring.